ENTREPRENEURS’ RATINGS OF FINANCE OPERATIONAL STRATEGIES NEEDED FOR IMPROVING THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study investigated entrepreneurs’ ratings of finance operational strategies needed forimproving the performance of small and medium enterprises in Delta State. A research questionsguided the study while null hypotheses was formulated. The descriptive survey research designwas adopted for the study. The study was conducted in Delta State. The population for this studyconsisted of 1,310 registered small and medium scale enterprises with the Delta State Ministryof Trade, Investment, Commerce and Industry. A sample of 393 entrepreneurs of small andmedium scale enterprises in Delta State was used for the study using proportionate stratifiedsampling technique. The instrument used for data collection was a 40-item questionnaire, whichwas validated by three experts. The instrument was subjected to test of internal consistencyusing Cronbach’s alpha method, and a coefficient of 0.83 was obtained. Mean and standarddeviation was used to answer the research questions while analysis of variance was used to testthe null hypotheses at 0.05 alpha level. The findings revealed that entrepreneurs rate financeoperational strategies as greatly needed for improving the performance of SMEs in Delta State.The finding also revealed that there was a significant difference in the mean ratings ofentrepreneurs on finance operational strategy needed for improving performance of SMEs basedon their years of experience. Based on the findings, it was recommended amongst others that theDepartment of Small and Medium Scale Enterprises with Delta State Ministry of Trade,Investment, Commerce and Industry should set up personnels to check up the financial internalcontrol system of small and medium enterprises.
Keywords: Operational strategies, finance, marketing, SMEs, performance.